A rainbow feast: new Asian short stories - Quayum, Mohammad Abdul (Marshall Cavendish, 2010)
A veritable collection of 25 short stories by young and prizewinning Asian writers from 15 countries: Japan, Taiwan, Vietnam, Laos, Malaysia, Singapore, the Philippines, Bangladesh, India, Pakistan, the UAE, Guyana, UK, USA and Australia.